Comparative immune responses of blue mussel and zebra mussel haemocytes to simultaneous chemical and bacterial exposure. Issue 135 (April 2023) - Gendre, Héloïse; Ben Cheikh, Yosra; Le Foll, Frank; Geffard, Alain; Palos Ladeiro, Mélissa
Abstract: Biomonitoring at the scale of the aquatic continuum and based on biomarkers, requires various representative species and a knowledge of their sensitivity to contaminants. Mussel immunomarkers are established tools for evaluating immunotoxic stress, but little is known about the consequences of an immune activation by local microorganisms on their response to pollution. This study aims to compare the sensitivity of cellular immunomarkers in two mussel species from different environments, the marine mussel Mytilus edulis (blue mussel) and the freshwater mussel Dreissena polymorpha (zebra mussel), to chemical stressors combined with bacterial challenge. Haemocytes were exposed ex vivo to the contaminants (bisphenol A, caffeine, copper chloride, oestradiol, ionomycin) for 4 h. The chemical exposures were coupled with simultaneous bacterial challenges ( Vibrio splendidus and Pseudomonas fluorescens ) to trigger activation of the immune response. Cellular mortality, phagocytosis efficiency and phagocytosis avidity were then measured by flow cytometry. The two mussel species had different basal levels since D. polymorpha showed higher cell mortality than M. edulis (23.9 ± 11% and 5.5 ± 3% dead cells respectively), and lower phagocytosis efficiency (52.6 ± 12% and 62.2 ± 9%), but similar phagocytosis avidity (17.4 ± 5 and 13.4 ± 4 internalised beads). Both bacterial strains led to an increase in cellular mortality (+8.4% dead cells in D. polymorpha, +4.9% in M. edulis ), as well an activation of phagocytosis (+9.2% of efficient cells in D. polymorpha, +6.2% efficient cells and +3 internalised beads per cell in M. edulis ). All chemicals triggered an increase in haemocyte mortality and/or phagocytotic modulations, except for bisphenol A. The two species differed in the amplitude of their response. The addition of a bacterial challenge significantly altered cell responses to chemicals with synergetic and antagonistic variations compared to a single exposure, depending on the compound used and the mussel species. This work highlights the species-specific sensitivity of mussel immunomarkers to contaminants, with or without bacterial challenge, and the necessity of considering the presence of in natura non-pathogenic microorganisms for future in situ applications of immunomarkers. Graphical abstract: Image 1 Highlights: Identical protocol allows to compare two mussel species immunomarker responses. Mussels have different basal levels of haemocyte mortality and phagocytosis. Chemicals and bacteria have different immunomodulatory effects. Bacterial challenge influence mussel haemocyte immune response to chemicals. D. polymorpha and M. edulis haemocytes respond differently to perturbations.